Salmonella spp. Inactivation During Hot Air Drying of Apples: Influence of Temperature, Bed Depth, and Air Velocity - Xiyang Liu; Elizabeth M. Grasso-Kelley; Alvin Lee; Lilybell Warda; Nathan M. Anderson (Journal of Food Protection)
Dried fruit has been linked to recalls and outbreaks due to microbiological hazards. While most drying processes are optimized for product quality, microbiological safety may not always be prioritized. The food industry is required to validate process preventive controls to ensure they significantly minimize or prevent microbial hazards. This study aimed to evaluate the combined effects of temperature, drying bed depth, and air velocity on the inactivation of Salmonella on apple cubes. A cocktail of six Salmonella serovars was inoculated onto fresh Gala apple cubes (∼0.256 cm3). A single layer of Salmonella-inoculated apple cubes was dyed red and placed atop un-inoculated cubes in a drying chamber to achieve final bed depths of 5.1, 8.9, or 12.7 cm. Apple cubes were dried at 88, 104, or 120 °C with air velocities of 2.10, 2.95, or 3.82 m/s. At multiple time points (n ≥ 5), samples were collected from the inoculated, dyed apple cubes on the top layer for water activity measurement and Salmonella enumeration. Across all drying conditions, an initial stable stage of apple aw and Salmonella populations was observed with varying durations followed by a rapid decrease in both. The overall effect of drying temperature, bed depth, and air velocity on microbial inactivation followed a consistent pattern: Higher temperature reduced the drying time required to achieve comparable Salmonella reductions as elevated product temperature enhanced microbial inactivation. Similarly, lower bed depth allowed the thinner apple layers to reach higher temperatures more rapidly, accelerating microbial reduction. Increased air velocity shortened the constant-rate drying period, promoted a faster temperature increase in the apple cubes, and resulted in higher lethality within a shorter drying period. Although a 5-log reduction of Salmonella was achieved at the end of drying under all but one condition, the reductions were reached at varying endpoint water activity levels.